Intimate partner violence: assessment, treatment and prevention - Evans, Richard (Domestic violence and abuse, 2021)
"Intimate partner violence (IPV) is a serious social problem affecting both men and women worldwide that can lead to a variety of negative mental and physical health effects. This book contains nine chapters that address the problem of IPV, exploring methods of preventing IPV as well as treatment for victims of IPV. Chapter One centers on the issue of blame, reviewing current research on the associations between self-blaming attributions and psychological outcomes among survivors of IPV. Chapter Two proposes a theoretical reflection on the phenomenon of domestic violence based on its understanding as a problem sustained by cultural beliefs and discourses and which can be tackled through education and the promotion of public debate, by means of institutional advertisements. Chapter Three highlights the importance of capacity building Brazilian police forces to tackle cases of IPV as well as to protect and enable victims to fully exercise their rights. Chapter Four argues that the Domestic Violence Risk instrument used by Portuguese police to assess IPV cases should be reworked, as it tends to assign a medium level of risk in cases that the scientific community would likely associate with high risk. Chapter Five discusses the relationship between IPV and academic stress. Chapter Six reviews research on factors affecting women's treatment engagement in the aftermath of IPV, including characteristics of the violence/violent relationship, types of mental health problems following IPV, and individual differences in personality and demographics. Chapter Seven deals with the coping mechanisms available to women living with HIV/AIDS in Tanzania who experience IPV. Chapter Eight details the relevance of methodological and ethical aspects of studies on violence involving children and how these requirements may affect research validity in this domain. Finally, Chapter Nine presents a study of violence against women media campaigns that use graphic imagery and how they impact fears of behaving assertively and of victimization, safety self-efficacy, and collective female self-esteem"--